Nestalik Yazı Konferansı - Alparslan, Ali, 1925-2006; İhsanoğlu, Ekmeleddin, 1943- (My University, 1987)
Nestalik hat yazı türü ve bu yazı sitilinde eser üreten hattatlar hakkında ayrıntılı bilgi toplantı kaydında yer almaktadır.
WAV and MP3 formats were created from the original audio cassettes along with the CD.
There is humming and intermittent gaps in the recording.
Keywords: Nastaliq script; Caligraphy; Calligraphers; Conferences